Ambiente para geração de trajetos de linhas de transporte público para análise de mobilidade e viabilidade de comunicação - Manika, Eduardo Renan (2022)
One of the main components of smart cities and urban mobility is public transport. Analyzing the behavior of public transport vehicles (buses) when they are moving along their path is important for research in this area. Collecting data for analysis considering the real world (the public transport buses themselves) requires a high amount of time and large amounts of financial resources. For this reason, the scientific community uses vehicular mobility simulators to generate vehicle displacements. Mobility simulators allow the researcher to import real maps of cities and simulate displacements. Importing the real maps of cities and their characteristics is done manually most of the time. However, generating realistic scenarios manually is very expensive (takes a lot of time). In the case of scenarios that involve public transport, generating them manually is even worse, as they have unique characteristics, such as: previously established vehicle trajectories, specific stopping points and defined departure times. Among the various simulators currently available, the Simulator of Urban Mobility (SUMO) stands out. This work aims to present an application capable of building the routes of public transport bus lines in SUMO automatically. This application was named EMMS (Mapping Schema for SUMO). Comparisons between simulation data and real data showed that EMMS was efficient in the map mapping process. Making use of EMMS, this work also presents a statistical analysis of data from vehicular mobility records of urban transport in the city of Curitiba (Paraná). Such analyzes aim to investigate the behavior of the network considering the possibility of communication (data exchange between vehicles). In addition, to investigate the type of application that can be performed in the networks formed by buses, studies were conducted considering the formation of an Ad Hoc Vehicular Network (VANET) in the studied environment. In general, the results reveal that the networks formed by buses (which make up a public transport system) have a high degree of partitioning and low performance in continuous end-to-end communication.